2018
DOI: 10.1038/s41388-018-0403-0
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of MUC20 suppresses the malignant character of pancreatic ductal adenocarcinoma cells through inhibition of the HGF/MET pathway

Abstract: Mucins are heavily glycosylated proteins that play critical roles in the pathogenesis of tumour malignancies. Pancreatic ductal adenocarcinoma (PDAC) is characterised by the aberrant expression of mucins. However, the role of mucin (MUC) 20 in PDAC remains unclear. PDAC is usually surrounded by a dense fibrotic stroma consisting of an extracellular matrix and pancreatic stellate cells (PSCs). The stroma creates a nutrient-deprived, hypoxic, and acidic microenvironment, and promotes the malignant behaviours of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…MUC20 is over-expressed in many cancers, and has been shown to regulate cell growth, differentiation, metastasis, adhesion, and invasive immune surveillance. MUC20 is also an independent prognostic factor for the poor survival rate of malignant tumors ( 26 , 27 ). In thyroid cancer, studies have found that MUC1, MUC4, and MU15 are overexpressed in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…MUC20 is over-expressed in many cancers, and has been shown to regulate cell growth, differentiation, metastasis, adhesion, and invasive immune surveillance. MUC20 is also an independent prognostic factor for the poor survival rate of malignant tumors ( 26 , 27 ). In thyroid cancer, studies have found that MUC1, MUC4, and MU15 are overexpressed in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism prediction of MET and RIPK2 in our study provides clues for basic research. Some studies have found that MET promotes malignant phenotypes and contributes to tumor growth of PDAC [ 29 , 30 ]. But it is still unclear whether MET is associated with autophagy activity in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, MUC1 and MUC4 have been extensively demonstrated to be oncomucins promoting tumor aggressiveness, proliferation, and metastasis [ 1 , 29 , 30 , 31 ], suggesting the potential use of their expression and methylation status as independent prognosis markers [ 32 , 33 , 34 ]. MUC16 and MUC20 have also been implicated in the malignant phenotype (cell viability, migration, and invasion) of PDAC cells [ 18 , 35 ]. MUC17 has been previously proposed as a potential prognosis molecular marker of PDAC [ 36 ].…”
Section: Discussionmentioning
confidence: 99%